SARS-CoV-2 viral load assessment in lung transplantation - Novysedlak, R; Vachtenheim, J; Stříž, I; Viklický, O; Lischke, R; Strizova, Z (Physiological research, 2021)
In the era of COVID-19 pandemic, organ transplantation programs were facing serious challenges. The lung transplantation donor pool was extremely limited and SARS-CoV-2 viral load assessment has become a crucial part of selecting an optimal organ donor. Since COVID-19 is a respiratory disease, the viral load is thought to be more important in lung transplantations as compared to other solid organ transplantations. We present two challenging cases of potential lung donors with a questionable COVID-19 status. Based on these cases, we suggest that the cycle threshold (Ct) value should always be requested from the laboratory and the decision whether to proceed with transplantation should be made upon complex evaluation of diverse criteria, including the nasopharyngeal swab and bronchoalveolar lavage PCR results, the Ct value, imaging findings and the medical history. However, as the presence of viral RNA does not ensure infectivity, it is still to be clarified which Ct values are associated with the viral viability. Anti-SARS-CoV-2 IgA antibodies may support the diagnosis and moreover, novel methods, such as quantifying SARS-CoV-2 nucleocapsid antigen in serum may provide important answers in organ transplantations and donor selections.
Keywords: virová nálož; hodnocení rizik; Male; Middle Aged; Risk Assessment; transplantace plic; Risk Factors; plíce; Adult; Tissue Donors; dospělí; mužské pohlaví; výběr dárců; dárci tkání; SARS-CoV-2; Viral Load; Lung; lidé; ženské pohlaví; Donor Selection; Humans; Bronchoalveolar Lavage Fluid; Lung Transplantation; rizikové faktory; prediktivní hodnota testů; bronchoalveolární lavážní tekutina; Female; testování na COVID-19; lidé středního věku; Predictive Value of Tests; COVID-19 Testing; COVID-19